Disease burden of fuelwood combustion pollutants in rural households of the Himalayas, India (Italian Journal of Public Health, 2012)
Background: Household biomass combustion for cooking purposes produces pollutants. Exposure tothese pollutants has various adverse health impacts and is a major contributor to global disease burden.However, a precise estimate of the burden attributable to biomass combustion at the local level is notavailable in different parts of the world, therefore restricting policymakers’ ability to develop targetedactions against the health hazards. a study was conducted in the rural Himalayas to generate informationabout disease burden, with the purpose of aiding the development of strategies to improve public health.MEtHods: Exposure level, population exposed and other relevant data regarding fuel-wood use, werecollected through questionnaire survey from 102 randomly selected households spread in 46 villages ina two phase cluster random sampling design study during 2008 – 09. the burden of disease for acuteLower respiratory Infection (aLrI), chronic obstructive Pulmonary disease (coPd) and Lung cancerwere estimated as per fuel-based approach of WHo guidelines for rural hilly households, using fuel-wood for cooking.rEsuLts: Households, primarily dependent on fuel-wood for fuel, had disability adjusted life years(daLYs) lost and deaths that were much higher than the national status. the incidence of disease burdenwas 2 909 daLYs lost, with a share of 1 987 for aLrI in children “up to” 5 years age, 730 for coPd and 192for Lung cancer in adults more than 30 years old, respectively.this result has implications for policy makers when deciding on an effective exposure reduction strategyand describes the risks connected between these health hazards and the health outcome of inhabitantsexposed to them. the paper also discusses the intervention strategies for “addressing” the issues rel-evant to fuel-wood generated exposure.
Keywords: Biomass; Exposure; Indoor air pollution; Pulmonary disease; Respiratory infection; Solid fuels